Problem-Based Learning Thematic Module for Enhancing Elementary Students’ Critical Thinking - Friscilla Sembiring (Yayasan Pustaka Karya Mandiri, 2026)
This study developed and evaluated a Problem-Based Learning thematic module for enhancing elementary students’ critical thinking skills at SD Negeri 065013. The study employed a Research and Development design using the ADDIE model, which included analysis, design, development, implementation, and evaluation stages. The product integrated contextual problems, PBL activities, student worksheets, evaluation tasks, and reflection activities. Validation involved material, media, language, and learning experts, while the classroom trial involved 30 elementary school students. Data were collected through expert validation sheets, teacher and student response questionnaires, observation sheets, project assessment rubrics, and critical thinking tests. The data were analyzed using validity analysis, practicality analysis, implementation analysis, descriptive statistics, N-Gain, and paired-sample t-test. The findings showed that the module was very feasible, with an average validation score of 87.75, very practical with an average score of 86.00, and well implemented with an average implementation score of 88.00%. Students’ critical thinking scores increased from a pretest mean of 54.37 to a posttest mean of 80.37, with a mean gain of 26.00 and an N-Gain of 0.57. The paired-sample t-test showed a significant improvement, t(29) = 271.14, p < .001. The study concludes that the module is feasible, practical, implementable, and effective for improving students’ critical thinking skills.